A Technology Adoption in MSMEs: A Literature Review Using Innovation Diffusion Theory (2023-2025) - Diah Utami Kusuma Wardani; Sambas Ade Kesuma; Iskandar Muda; Firman Syarif (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2026)
This study conducts a Systematic Literature Review (SLR) to synthesize recent research on the application of the Diffusion of Innovation (DOI) Theory in analyzing technology adoption among SMEs and micro enterprises. A total of 37 peer-reviewed articles published between 2023 and 2025 were examined to identify research trends, thematic focuses, and challenges in innovation diffusion. The findings indicate a growing application of DOI driven by increasing digitalization and the pursuit of innovation-based competitiveness. Four major themes emerge: digital technology adoption, organizational readiness, environmental and institutional influences, and post-adoption performance outcomes. Results show that innovation adoption enhances efficiency, performance, and market reach but is hindered by limited resources, digital skill gaps, and infrastructural constraints. Despite these challenges, DOI remains a robust theoretical framework for understanding technology diffusion in resource-limited enterprises. The study contributes by consolidating recent DOI applications and offering practical insights to support policymakers and practitioners in advancing MSME digital transformation. Keywords: Diffusion of Innovation Theory, Technology Adoption, MSMEs